Tributyltin chloride leads to adiposity and impairs metabolic functions in the rat liver and pancreas - Bertuloso, Bruno D. (2015)
Tributyltin chloride (TBT) is an environmental contaminant used in antifouling paints of boats. Endocrine disruptor effects of TBT are well established in animal models. However, the adverse effects on metabolism are less well understood. The toxicity of TBT in the white adipose tissue (WAT), liver and pancreas of female rats were assessed. Animals were divided into control and TBT (0.1. μg/kg/day) groups. TBT induced an increase in the body weight of the rats by the 15th day of oral exposure. The weight gain was associated with high parametrial (PR) and retroperitoneal (RP) WAT weights. TBT-treatment increased the adiposity, inflammation and expression of ERα and PPAR. γ proteins in both RP and PR WAT. In 3T3-L1 cells, estrogen treatment reduced lipid droplets accumulation, however increased the ERα protein expression. In contrast, TBT-treatment increased the lipid accumulation and reduced the ERα expression. WAT metabolic changes led to hepatic inflammation, lipid accumulation, increase of PPAR. γ and reduction of ERα protein expression. Accordingly, there were increases in the glucose tolerance and insulin sensitivity tests with increases in the number of pancreatic islets and insulin levels. These findings suggest that TBT leads to adiposity in WAT specifically, impairing the metabolic functions of the liver and pancreas.